A systematic evaluation of five different image-derived input functions for the clinical implementation of 18F-NaF bone PET/CT in patients with chronic kidney disease–mineral and bone disorder - Theil, Jørn; Vrist, Marie Houmaa; Bech, Jesper Nørgaard; Fynbo, Claire Anne (Frontiers in Nuclear Medicine, 2023)
Introduction: The aim of this study was to investigate the impact of the use of varying input parameters on resulting bone plasma clearance (Ki) and other kinetic modelling parameters in a group of patients with chronic kidney disease – mineral and bone disorder (CKD-MBD). Methods: Raw PET/CT data and blood data was systematically analyzed using five different VOIs for the input functions in the left ventricle and in the thoracic aorta. Standardized VOIs were placed in four thoracic vertebrae and the results pooled and averaged. The basic image derived input functions (IDIFs) were corrected for partial volume effect and spill-over and modified by substitution of the terminal image exponential with the corresponding plasma-exponentials derived from blood samples. Ki was then calcu-lated both using non-linear regression (NLR) analysis and graphical Patlak-analysis and compared. Results: Our original results were reproducible with an inter-observer difference of about 6%. The cor-rection factors varied with the VOI-volumes from 0.73 ± 0.17 for the largest LV-VOI (48.7 ± 25.3 cm3) to 0.99 ± 0.10 for the AO-VOI (3.4 ± 1.2 cm3). The average NLR-Ki-results ml/min∙ml-1 varied between 0.0378 ± 0.0112 ml/min∙ml-1 and 0.0432 ± 0.0095 ml/min∙ml-1 with fixed-vB and 0.0408 ± 0.0111 ml/min∙ml-1 and 0.045 ± 0.0102 ml/min∙ml-1 with free-fitted vB. The corresponding Patl-Ki-results varied between 0.0302 ± 0.0071 ml/min∙ml-1 and 0.0325 ± 0.0070 ml/min∙ml-1 having lesser differences and variances. The input functions with least variance and mean-differences compared with NLR-results were derived from the left ventricle with a VOI-volume of 19.2 ± 11.3 cm3 corrected for PVE and Bg with Ki-mean-difference: 0.0097 ± 0.0370 ml/min∙ml-1 and 95%-confidence limits [-0.023;0.004]. Conclusions: Our results indicated that a VOI with a volume of about 20 cm3 with a correction factor of 0.83 ± 0.13 results in Patlak-results with the least variance and difference compared with the NLR-results. The use of free-fitted vB in NLR-analysis showed the most robust results in all input series. The Patlak-results were in comparison generally lower than the NLR-results (-17.3% to -23.4%) but very robust across the various input-series and with results comparable to previously published data and are therefore recommended for future analysis.